Enhancing social interaction in depression (SIDE study): protocol of a randomised controlled trial on the effects of a Cognitively Based Compassion Training (CBCT) for couples - Aguilar-Raab, Corina; Jarczok, Marc N.; Warth, Marco; Stoffel, Martin; Winter, Friederike; Ditzen, Beate (BMJ open, 2018)
Introduction: Positive social interactions (PSIs) and stable relationships can exert substantial benefits on health. However, patients suffering from depression benefit less from these health-promoting effects. Moreover, relationship quality and even partners’ health has been found to be negatively affected by depressive symptomatology, which may result in overall impairments in social functioning of a romantic couple. Psychobiological research indicates that these impairments may be accompanied by a maladaptive regulation of the patient’s neuroendocrine response to external stressors. Concerning the improvement of social functioning, first studies showed promising results of “Cognitively Based Compassion Training (CBCT®)”. However, randomised trials are still scarce. Previous programmes did not involve participation of the patient’s romantic partner. Therefore, the present study aims to investigate whether a CBCT® programme adapted for couples (CBCT®-fC) can improve depressive symptoms, distress, social interaction skills and the neurobiological regulation of stress. Methods and analysis: Couples with the female partner suffering from depression will be invited to participate in a pre-to-post intervention assessment on two consecutive days, respectively, involving a standardised PSI task, eye-tracking, ECG recordings, saliva-sampling, blood-sampling and questionnaire data. After baseline assessment, participating couples will be randomised to either a 10 week CBCT®-fC or to a treatment as usual control condition. The primary endpoint is the reduction of depressive symptoms measured by the Hamilton Depression Rating Scale. Secondary outcomes encompass self-rated depression (Beck Depression Inventory), attention towards the partners face during PSI (eye tracking), stress-related biomarkers (cortisol, α-amylase, interleukin (IL)-1ß/IL-6, heart rate variability), methylation of oxytocin-receptor-genes and serotonin-transporter-genes and self-ratings of psychological constructs such as relationship quality and empathy. Ethics and dissemination: Ethical approval has been obtained by the Ethics Committee of the Medical Faculty Heidelberg. Results will be presented in international, peer-reviewed journals and on conferences in the field of clinical psychology and psychiatry. Trial registration number NCT03080025.